PENGARUH KOMPENSASI FINANSIAL TERHADAP KINERJA MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING DI PT AMAAN SITUBONDO - Rianti, Sheilla Maulida; Karnadi, Karnadi; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
One of the important factors in the field of human resources is to provide financial compensation and motivation which is the right of employees and the company's obligation to support the contribution of workers in order to achieve the goals that have been determined. The purpose of this study was to analyze and examine the effect of Financial Compensation on Performance through Motivation as an intervening variable at PT. AMAAN Situbondo. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that financial compensation has a significant positive effect on motivation, financial compensation has a significant positive effect on performance, motivation has a significant positive effect on performance, financial compensation has a significant positive effect on performance through motivation